Investigation of Genital System Cancers Prevalence in Isfahan, Iran - Zahra Tolou-Ghamari (National Cancer Center - Dharmais Cancer Hospital, 2019)
Background: Previous publication reported a significant disparity of genital cancer incidence between genders. The aim of this study is to investigate period prevalence (PP) and incidence (Irs) of genital cancer in Isfahan/Iran. Methods: Information equivalent to those collected by the USA Surveillance, Epidemiology, and End Results (SEER) program was obtained from the Isfahan Cancer Registry. Period prevalence (PP) was calculated per 100.000 persons. The cancer sites studied were defined according to the International Classification of Diseases (ICD-O; Third Edition) and recorded by topography code. Results: Between the years 2011 to 2015, among all registered cases (3024 cases), 60% applied to the male genital system. The mean (SD) age at diagnosis was higher for men 69.4 (14.7) than women 57.8 (15) (t-test; P<0.006). The calculated PP was significantly (Chi-squared test; P<0.001) higher in males (71.5) than females (49.6) per 100.000 in Isfahan Province. Conclusions: The PP for ovarian cancer in female and prostate cancer in male was higher than for other genital tumors. To facilitate early diagnosis for better management, we recommend that health-care plans for Isfahan Province/Iran place a greater focus on pharmacotherapy and environmental factors in cancer control.